Auxiliary solar heating system: simulation and control (Research, Society and Development, 2020)
Solar energy has become the most used forms of alternative energy, being a renewable and non-polluting source. As such, solar heating systems have been increasingly used in the residential and industrial sectors. However, in periods with low or no solar luminosity, its efficiency is impaired. Based on this assumption, this work proposes the mathematical modeling of an auxiliary heating system, using solar energy as an alternative source. Three types of configurations are evaluated for the heating system: system I - without solar collector, system II - with solar collector running 24 hours a day, and system III - hybrid system, in which solar collector is activated only during the period in which there is incidence of solar radiation (10am - 5pm). It is proposed the implementation of on/off and PI controllers, in the configurations studied. The results are obtained from the simulation of the mathematical model using the free software Scilab®. The results show that the hybrid system is saving more energy, about 8% of energy when compared to the system I. The PI control is best suited for this application, especially when it is implemented with hybrid system, saving of 60W of energy per day of operation.